Monoenergetic High-Energy Ion Source via Femtosecond Laser Interacting with a Microtape - X. F. Shen (American Physical Society, 2021)
Intense laser-plasma ion sources are characterized by an unsurpassed acceleration gradient and exceptional beam emittance. They are promising candidates for next-generation accelerators towards a broad range of potential applications. However, the laser-accelerated ion beams available currently have limitations in energy spread and peak energy. Here, we propose and demonstrate an all-optical single laser scheme to generate proton beams with low spread at about 1% level and hundred MeV energy by irradiating the edge of a microtape with a readily available femtosecond petawatt laser. Three-dimensional particle-in-cell simulations show that when the electron beam extracted from both sides of the tape is injected into vacuum, a longitudinal bunching and transverse focusing field is self-established because of its huge charge (about 100 nC) and small divergence. Protons are accelerated and bunched simultaneously, leading to a monoenergetic high-energy proton beam. The proposed scheme opens a new route for the development of future compact ion sources.